Viral protein requirements for efficient human parainfluenza virus 3 virus-like particle formation - Bracken, Megan (My University, 2011)
Enveloped viruses exit infected cells after the genome and specific viral proteins assemble at the cell membrane and bud from the host cell as infectious virions. To investigate the process by which human parainfluenza virus 3 (HPIV-3) proteins assemble and release, viral proteins were expressed in 293T cells individually or in combination to produce virus-like particles (VLPs). When the HPIV-3 matrix (M) protein was expressed individually; enveloped VLPs containing M protein were released from cells, indicating that M protein is critical for virus particle budding. When viral envelope proteins hemagglutinin-neuraminidase (HN) and fusion (F), as well as RNAbinding nucleoprotein (N), were expressed individually, these proteins could not trigger their own release from cells. However, when M protein was coexpressed with HN, F, or N, VLPs that contained M and HN, M and F, and M and N, respectively, released from cells. M protein release was not enhanced by coexpression of other viral proteins. Electron microscopy analysis verified that VLPs were morphologically similar to HPIV-3 virions. These findings suggest that M protein interacts with the HN, F, and N proteins and plays a coordinating role in HPIV-3 virus particle assembly and release.
Keywords: Electron microscopy.; Parainfluenza.; Virus diseases.